Otimização da extração assistida por ultrassom de compostos antioxidantes da erva mate (Illex paraguariensis St. Hill) para uso na estabilização oxidativa do biodiesel - Peters, Alini Rafaela Neitzke (2022)
Seeking to obtain less environmental impact, the use of biodiesel has become a way to replace diesel. Biodiesel is a renewable fuel and can be manufactured from different raw materials, one of which is soybean oil. This fuel suffers from the oxidation process due to the presence of fatty acids in its composition, and in order to minimize this oxidation process, antioxidants are used. Synthetic antioxidants are usually used, which are expensive and have harmful characteristics for the environment. Thus, the use of natural antioxidants becomes a viable way to replace synthetic ones. In this work, we sought to evaluate the oxidative stability of biodiesel B100 using the extract obtained from yerba mate as an antioxidant. For the extraction of yerba mate antioxidants, maceration, Soxhlet and ultrasound methods were tested. In the ultrasound-assisted extraction method, it was sought to optimize the process by varying the parameters potency (%), temperature (°C) and solvent/herb ratio (mL.g-1). The total flavonoid and phenolic contents of the samples, as well as their antioxidant capacity, were determined using the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and the iron-reducing antioxidant (FRAP) methods. The values at the optimal point of ultrasound-assisted extraction were: Rend=19.93%, flavonoids=70.12 mg EQ·gextrate-1, phenolics=92.69 mg EAG·gextrate-1, FRAP=1915.8 μmol EFe2+·gextrate-1 and DPPH=495.82 μmol ETrolox·gextrate-1, as well as the operating conditions that lead to the optimal response: T= 52.75ºC, P= 77% and RSE= 11.25 mL.g-1. The global desirability function achieved in the optimization was 0.8928. Biodiesel produced in the laboratory from commercial soybean oil was characterized and subsequently tested for its oxidative stability using the accelerated oxidation method at 110°C in Rancimat equipment. Biodiesel did not meet the minimum limit established by the National Petroleum Agency (ANP), which requires 12 hours of induction. The tested extract did not show satisfactory results in the replacement of synthetic antioxidants.